The New Role of the Client in Adopting Innovation in Construction Projects - AL-TAYEH, TAREQ FAROUQ (2017)
The rate of innovation adoption in the construction industry has been witnessed to have risen due to an increased awareness in clients about the perceived benefits of innovation. Two important innovation examples that have been adopted by many construction clients in recent years were explored, which are: Building Information Modeling (BIM) and Prefabrication. The construction client`s role in the traditional procurement method, which is considered the dominant procurement method in the construction industry, has been witnessed to have changed towards driving construction industry stakeholders to adopt innovation in construction projects. The new role of the construction client is that of innovation co-creator in which the client plays the pivotal role of diminishing the barriers which exist under the traditional procurement method’s hierarchy and inducing the construction project stakeholders to work closely and collaboratively to co-create innovation. The literature investigated the diffusion of innovation in the construction industry which revealed seven factors which have been influencing the change in the client’s role towards a new role of co-creating innovation in construction projects. These factors were used to derive the research hypotheses. The quantitative research approach was implemented in this research to examine the defined hypotheses through a survey which was collected from 107 professionals presenting different organizations working in the United Arab Emirates construction industry. The data analysis results revealed that there are six factors which influence the change in the construction client’s role towards the adoption of innovation in construction projects in the United Arab Emirates, which are: performance improvement, environmental sustainability, client characteristics, organizational culture, client experience and competence, and government regulations. The research concluded that the aforementioned six factors are influencing change in the construction client’s role under the traditional procurement method towards the new role of co-creating innovation in construction projects in the United Arab Emirates.